FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK PERATAAN LABA - Fabian Asri, 0935030513 Roni; Badjuri, Achmad (Students Journal of Accounting and Banking, 2012)
The  goal  of  this  research  is  to examine  the  influence  of  company  factors toward income smoothing practice among listed companies at Indonesian stock exchange during 2008-2010.  The  factors  being  examined  are company  size,  financial  leverage,  institution ownership,  and  profitability.  The  population  in this research uses 204 manufacturing company listed  in  Indonesian  stock  exchange  during 2008-2010.  The  sample    also  uses  a  purposive sampling  technique.  The  data  analysis  for  this research  is  using  spss  17,0 for windows.  Eckel index  is  used  to  spesificate  income  smoothing practice.The  result  of  this  research  shows  that size  of  company  has  significant  influence  to income  smoothing  practice.  But, financial leverage,  institutional ownership  and profitability  variables  do  not  have  significant influence to income smoothing practice.Keywords: company  size,  financial  leverage, institution  ownership,  profitability  and  income smoothing practice.